Indictment of the Accused in Absentia - Ghazinyan, Gagik; Mkrtchyan, Petik (Bulletin of Yerevan University C: Jurisprudence, 2023)
The article concerns the essence and features of the presentation of charges in proceedings carried out in the absence of the accused (correspondence proceedings).The authors turn to the grounds and conditions for bringing charges in the course of proceedings carried out in the absence of the accused, to the opinions expressed in theory regarding the institution in question.The regulations of the institution in question are presented in the national criminal procedure legislation and comparisons of regulations provided for by the legislation of foreign countries are carried out.The article also presents the positions of the European Court of Human Rights on this issue, and in their light discusses the theoretical problems of bringing charges in absentia.The subject of discussion is also the question of when the preliminary investigation body knows the exact location of the accused, whether the latter should take measures to notify the accused of the day and time of the indictment, and only in case of his failure to present the charge in absentia.In connection with the formulation of the question, the authors come to the conclusion that when there are grounds and conditions for absentee proceedings, and the investigator decides to carry out absentee proceedings, then charging the accused by video does not follow from the general ideology of absentee proceedings.
Keywords: proceedings; absentee; indictment; change of charges; video communication; international mutual assistance; public notification; removal of the defender from the proceedings